PENINGKATAN MUTU PENGAJARAN BAHASA INGGRIS MELALUI PELATIHAN GURU BAHASA INGGRIS SE KABUPATEN GORONTALO: PENINGKATAN MUTU PENGAJARAN BAHASA INGGRIS MELALUI PELATIHAN GURU BAHASA INGGRIS SE KABUPATEN GORONTALO - nur wahidah thayib pido; Enni Akhmad (Madani: Jurnal Pengabdian Ilmiah, 2022)
This research aims to generate English teachers who can comprehend and use blended learning methods. The purpose of this Classroom Action Research (CAR) study is to enhance the knowledge and comprehension of English subject teachers regarding using the blended learning model in the learning process. This study investigated how considerably English teachers' knowledge and comprehension of the blended learning model increased due to the training. This course also includes information about the blended learning paradigm, which mixes face-to-face learning (direct interaction) with online learning, for instance, through social media such as WhatsApp, Facebook, Twitter, Telegram, Skype, and Teleconference. The results indicated that many participants were unfamiliar with the most recent learning applications.